2012 IEEE Symposium on Business, Engineering and Industrial Applications 2012
DOI: 10.1109/isbeia.2012.6422992
|View full text |Cite
|
Sign up to set email alerts
|

The Granger causality effect between the stock market and exchange rate volatility in the ASEAN 5 countries

Abstract: The issue of inter-relation between stock returns and exchange rates has often been discussed by economists since they both play important roles in influencing the development of a country's economy. The specific objective of the study is to identify the Granger causality effect between the stock market and exchange rate volatility in the ASEAN 5 countries. In order to capture the interactions between stock market performance and exchange rate volatility, the multivariate vector autoregression (VAR) framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Empirical evidences have shown causation from exchange rate to stock market prices (Abdalla and Murinde (1997) for Pakistan; Erbaykal and Okuyan (2007) for eight countries out of thirteen countries; Yusuf and Rahman (2012) for Malaysia; Olugbenga (2012) for Nigeria) as well as causation from stock market prices to exchange rate (Erbaykal and Okuyan (2007) for five countries out of thirteen countries; Yusuf and Rahman (2012) for Thailand). The studies have also found bidirectional causality (Erbaykal and Okuyan (2007) for three countries; Yusuf and Rahman (2012) for Malaysia). However, there are some evidences of no causation between exchange rate and stock market prices (Asaolu and Ogunmuyiwa, 2011;Zia and Rahman, 2011).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…Empirical evidences have shown causation from exchange rate to stock market prices (Abdalla and Murinde (1997) for Pakistan; Erbaykal and Okuyan (2007) for eight countries out of thirteen countries; Yusuf and Rahman (2012) for Malaysia; Olugbenga (2012) for Nigeria) as well as causation from stock market prices to exchange rate (Erbaykal and Okuyan (2007) for five countries out of thirteen countries; Yusuf and Rahman (2012) for Thailand). The studies have also found bidirectional causality (Erbaykal and Okuyan (2007) for three countries; Yusuf and Rahman (2012) for Malaysia). However, there are some evidences of no causation between exchange rate and stock market prices (Asaolu and Ogunmuyiwa, 2011;Zia and Rahman, 2011).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…It provides information about direct and indirect influences between channels representing the direction of information flow [8]. The notion of Granger causality (GC) [9] based on MVAR model, has been extensively employed to investigate directional influences within coupled variables of dynamical systems in various areas, such as climate studies [10], [11], economics [12], [13] and neuroscience [14], [15]. If prediction of any time-varying process X can be enhanced by considering the past information of another time-varying process Y instead of the past information of process X alone, then the process Y is said to granger cause process X.…”
Section: Introductionmentioning
confidence: 99%